Turbulence consideration in wind turbine design and its effect on main shaft motion and blade root strain - Lutschinger, Dirk (Curtin University, 2016)
This PhD research investigated the influence of turbulence effects on the vibration behaviour of wind turbines. A small laboratory scale wind turbine test facility was developed with special purpose instrumentation and sensors. Experimental investigations of the vibration behaviour of the turbine demonstrated the complexity of the displacements of the main rotor shaft and the strain at the roots of the rotor blade. This research will assist in the ongoing development of improved failure detection mechanisms.